Statistical Optimization of Medium Components of Xylanase Production by Irpex lacteus BAFC 1168 strain F under liquid fermentation - Díaz, Gabriela v (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2015)
The enhanced xylanase production of white rot fungus Irpex lacteus BAFC 1168 strain F using a liquid fermentation culture was investigated. The media nutrients were screened by a Plackett-Burman design and from the analysis of variance, carboxy-methylcellulose, urea and peptone were found to be the most positive and significant nutrient components. Hence, these three variables were selected for further optimization using a five-level central composite design in response surface methodology. The validation of the model experiment was conducted reaching 8.29 U/mL of xylanase activity when the composition medium was 1.6 g/L of CMC, 0.84 g/L of urea and 2 g/L of peptone. Optimum temperature and pH conditions on xylanase activity were also determined using a central composite design. It was reached a maximum xylanase activity of 8.36 U/mL when temperature and pH were 42.8°C and 5.6, respectively.